Audit assurance and tax enforcement: A comparative study of Central-Eastern European countries. Issue 4 (2nd October 2019) - Zhang, Dengjun
Abstract : Purpose: The purpose of this paper is to examine the impact of audit assurance on tax enforcement, which is represented by whether firms have been visited by tax officials and, if so, the total number of inspections per fiscal year. The efficiency of tax administration is further examined by whether it becomes a binding constraint to a firm's operations. Design/methodology/approach: The sample consists of 18, 746 firm-year observations from 28 transition and market-based economies in Central-Eastern Europe. The binary logit model, the Poisson model and the ordinal logit model are applied to test the hypotheses. Findings: The empirical results show that, while audit assurance does not reduce the probability of being visited by tax officials (regardless of visit times) for the two country groups, firms with audited financial reports meet tax officials less often in market-based economies but not in transition economies. Furthermore, only in market-based economies does audit assurance reduce the probability that tax administration becomes a severe obstacle to firms' operations. Originality/value: This study addresses the relationship between tax administration and audit assurance in market-based and transition countries. One implication of the empirical findings is that audit assurance would add benefits to business environments when countries evolve from transition to market-based economies.